ROLE OF ARYL HYDROCARBON RECEPTOR NUCLEAR TRANSLOCATOR IN DIABETES MELLITUS AMONG RAICA AND NON-RAICA COMMUNITIES OF RAJASTHAN - Jain, Mili; Vyas, Raj Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This study was conceptualized to assess genotypic factors associated with a lower prevalence of type-2 diabetes mellitus in Raica community of Rajasthan, India. Methods: In this study, 114 people from Raica community and 150 people from non-Raica community were recruited. Their demographic details age and sex, anthropometric data body mass index, and waist-to-hip ratio, and laboratory parameters such as fasting blood glucose (FBG), HbA1c, and physiological parameters of systolic and diastolic blood pressure were taken into consideration. Results: In the present study, there were 40 females and 74 males from Raica community and, 52 females and 98 males from non-Raica community. The mean age was 41.14 and 46.93 in Raica and non-Raica communities. The FBG, HbA1c levels, and physiological parameters were significantly lower in Raica community (p<0.05). The AG allele of the Aryl hydrocarbon receptor nuclear translocator gene was more frequently seen in individuals with lower FBG and no individual studied, had the AA allele. Conclusion: The genetic polymorphism studied has the same frequency of distribution in both Raica and non-Raica people with or without diabetic conditions. The leanness and better control over the glucose levels in the Raica community are supposed to be key factors in lowering diabetes mellitus prevalence.